Fractional Holographic Dark Energy in Self-Creation Theory and Lyra Geometry - Rautkar, D.; Raut, V. B. (Journal of Scientific Research, 2025)
In this paper, fractional holographic dark energy in self-creation theory and Lyra geometry have discussed the exact solution of Einstein's field equations for LRS Bianchi type- I cosmological model. In order to obtain a determinant solution, special law of variation for Hubble’s parameter proposed by Berman (1983) has been considered. For each model, we evaluate key dynamical parameters, including the equation of state (EoS) parameter, the deceleration parameter and the total energy density parameter of dark energy. Our findings indicate that these models describe an accelerated expansion of the universe, with theoretical results showing reasonable agreement with observational data.